Coexistence of metabolic syndrome and osteopenia associated with social inequalities and unhealthy lifestyle among postmenopausal women in South Korea: the 2008 to 2011 Korea National Health and Nutritional Examination Survey (KNHANES). Issue 6 (June 2020) - Lee, Hansongyi; Kim, Jieun; Lim, Hyunjung
Abstract: Objective: The prevalence of metabolic syndrome (MetS) and osteoporosis (OP) among postmenopausal women has been rapidly increasing. We examined the associations between socioeconomic status-related factors, unhealthy lifestyle, and the coexistence of MetS and osteopenia or OP. Methods: One thousand nine hundred ninety-one postmenopausal women aged 45 to 65 years were used to select a representative sample of the civilian, noninstitutionalized South Korean population from the 2008 to 2011 Korea National Health and Nutrition Examination Survey data. Women were grouped as neither MetS nor OP (normal), MetS, OP, and both MetS and OP (MetS + OP). Socioeconomic status (education, household income, place of residence, employment status), health-related behaviors (physical activity, alcohol consumption, smoking), and diet-related factors (intake of nutrients and food groups, eating habits, food insecurity) were obtained. Logistic regression models were used to examine the odds ratio (OR) and 95% confidence interval (CI). Results: The prevalence of MetS + OP was 32.5%. The average number of MetS risk factors in MetS + OP was 3.5, higher than that of normal and OP groups ( P < 0.001). Bone mineral density at all sites was significantly lower in MetS + OP than normal and MetS groups ( P < 0.001). Also, calcium, phosphorus, vitamin A, riboflavin, and niacin levels were lowest in the MetS + OP group compared with the three other groups ( P < 0.05). After controlling for covariates, low-income and low-education women were more likely to have MetS + OP (OR 1.97, 95% CI 1.04-3.72); high-income and high-education group was 70% less likely to have MetS + OP (OR 0.30, 95% CI 0.10-0.86) compared with the middle-income and middle-education group. Conclusions: Social inequalities might be powerful contributors in Korean postmenopausal women with coexistence of MetS and OP. Therefore, social and political perspective approaches are required in this population for prevention and treatment of MetS and OP. Future studies should explore to find controllable factors and thereby improve health status in postmenopausal women.